Plumbagin, a Plant-Derived Compound, Exhibits Antifungal Combinatory Effect with Amphotericin B against Candida albicans Clinical Isolates and Anti-hepatitis C Virus Activity - Hassan, Sherif T S; Berchová-Bímová, Kateřina; Petráš, Jan (Phytotherapy research, 2016)
Plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone), the major active constituent of Plumbago indica L., has been shown to be effective against a wide range of infectious microbes. In this study, plumbagin has been evaluated in vitro for its antifungal combinatory effect with amphotericin B against Candida albicans (C. albicans) clinical isolates and anti-hepatitis C virus (HCV) activity. Antifungal activity was determined by broth microdilution method, and combinatory effect was evaluated by checkerboard assay according to ΣFIC indices, while cytotoxicity was determined by MTT assay. Anti-HCV activity was determined in infected Huh7.5 cells using quantitative real-time reverse transcription PCR, and cytotoxicity was evaluated by MTT assay. Plumbagin exerted inhibitory effect against all C. albicans strains with minimum inhibitory concentration values ranging from 7.41 to 11.24 µg/mL. The additive effect of plumbagin when combined with amphotericin B at concentrations of (0.12, 0.13 and 0.19, 1.81 µg/mL, respectively) was obtained against five of seven strains tested with ΣFIC ranging from 0.62 to 0.91. In addition, plumbagin was found to be used safely for topical application when combined with amphotericin B at concentrations corresponding to the additive effect. Plumbagin exerted anti-HCV activity compared with that of telaprevir with IC50 values of 0.57 and 0.01 μM/L, respectively, and selectivity indices SI = 53.7 and SI = 2127, respectively. Our results present plumbagin as a potential therapeutic agent in the treatment of C. albicans and HCV infections. Copyright © 2016 John Wiley & Sons, Ltd.
Keywords: antifungální látky; Candida albicans; antimicrobial agents; fungal infection; amfotericin B; Naphthoquinones; Humans; Antifungal Agents; natural products; HCV infection; Amphotericin B; naftochinony; plumbagin; lidé; Hepacivirus